The Faroese Cultural Archive: The Archive as a Source and Theme in Local Historical Writing - Moberg, Bergur Rønne (Scandinavistica Vilnensis, 2023)
The cultural Faroese archive consists mostly of local historical writing. This article focuses on works of local history and claims that the local historical part of the archive constitutes the most extensive part of Faroese writing conventions. In publications on local history, the archive progresses into book form without undergoing any significant interpretation. This phenomenon is examined here as an expression of the archive as active and as an element of access, but one that is still used in a traditional cultural-historical context. However, what does “archive” really mean in this context? As a central writing convention, the cultural Faroese archive transcends common notions of the archive as collection, registration and unpublished source material. The article examines the cultural Faroese archive as both source and theme. In other words, it distinguishes between 1) the original archives as sources, which are kept in museums and libraries without being published, and 2) the use of archival sources as topics and cultural resources within published works. Through employing an elastic conception, the article understands the archive as a metaphor in Faroese writing conventions. On this basis, it argues that Aleida Assmann’s distinction between the archive as a source and subject cannot be maintained in a Faroese context because the sources per se are treated as a cultural-historical subject. Finally, it contends that the active and totalizing dimension in the cultural Faroese archive transcends abstract notions of the archive among leading archival theorists, who potentially disregard the cultural archive. Their view is countered by a study of the archive as a felt, experienced and interpreted cultural reality related to the Faroe Islands as a specific, ultraminor, geographical entity. By making geography an independent explanatory factor – and not only as a metaphor for a powerful centre and a powerless periphery, as in classical postcolonialism – it is possible to see connections between size and structure. In the case of the Faroese archive, the (colonial) order of things cannot be understood fully without acknowledging the relations between size and structure. The size of the Faroese cultural archive is associated with a lack of capacity, which in turn contributes to an understanding of Faroese uses of it. This power of action in ultraminor cultures is treated as a willingness to compensate for their shortcomings. Thus, what seems to be deprivation only turns out to be cultural capital.
Keywords: Faroe Islands; local historical writing; cultural archive; total archive; elastic archive